Study guides

☆☆

Q: Evaluate x-2 for x -3.

Write your answer...

Submit

Still have questions?

Related questions

x3 + ax + 3a + 3x2 = x (x2 + a) + 3 (a + x2) = x (x2 + a) + 3 (x2 + a) = (x2 + a)(x + 3) Checking the work: x3 + ax + 3x2 + 3a or x3 + 3x2 + 3a + ax = x2 (x + 3) + a (3 + x) = x2 (x + 3) + a (x + 3) = (x + 3)(x2 + a)

It is x*x + y*y*y*y

(x + 3)(x - 3)

7

x3 + x2 - 3x - 3 x(x2 + x - 3) - 3

14

-x2 = x - 6 x2 + x - 6 = 0 (x - 2)(x + 3) = 0 x ∈ {-3, 2}

x2 + 2x - 3 = (x + 3)(x - 1)

x2-9 = (x-3)(x+3) when factored

9 - x2 will factor into (3 - x)(3 + x)

x2 + 2x = 3 x2 + 2x - 3 = 0 (x + 3)(x - 1) = 0 x ∈ {-3, 1}

To evaluate a function means to replace the variable with some value, and calculate the value of the function. For example, in the parabola y = x2 (or, using functional notation, f(x) = x2), if you replace x with 10, and calculate x2, you are evaluating the function for that specific value.

People also asked